Internet of things (IoT) in nano-integrated wearable biosensor devices for healthcare applications - Verma, Damini; Singh, Kshitij RB; Yadav, Amit K.; Nayak, Vanya; Singh, Jay; Solanki, Pratima R.; Singh, Ravindra Pratap (Biosensors and bioelectronics. X, 2022)
An individual's health is one of the essential aspects of life, but due to the limited technology at health care centers, many people face various restrictions during their treatment. These days, Internet-of-Things (IoT) is the most fascinating topic that provides solutions to these limitations in various ways. The IoT is utilized in various healthcare conducts that include detection, treatment, and monitoring of diseases. Wearable devices are a part of IoT that is proposed for helping patients to get the correct treatment. The conventional communication networks developed for humans-based applications face many issues like stringent latency, restricted computing capability, and short battery life. On the other hand, the onset of 5G has developed a new set of technologies that offer the vital "backbone” for connecting to the billions of devices for the upcoming IoT that would completely modify our professional and private lives. Due to the data capabilities, intelligent management, and superfast connectivity of 5G, this network has enabled new health care opportunities that include treatment, data analytics, diagnostics, and imaging. In the current review, a systematic literature survey of IoT, IoT-based wearable devices, and the role of 5G in IoT for healthcare is described in detail. Furthermore, we have explained the usage of wearable devices in detecting the issue in terms of healthcare, such as curing, monitoring, and detection of disease. Nevertheless, this review article also emphasizes the employment of IoT architecture and its wearable devices in addition to the upcoming research challenges related to this area. •The trending Internet of Things (IoT)-based wearable technologies that were used in recent years have been discussed.•An IoT-based wearable devices were indorsed to encourage its forthcoming applications in healthcare.•IoT technologies assumed to be one of the key pillars of the fourth industrial revolution in innovations.•Wearable devices, such as smart watches and fitness bands, have become part of the everyday life.•The impact of 5G on Internet of Medical Things (IoMT), IoT and IoT-based wearable devices have been discussed. [Display omitted]